Regulatory mutations in the A2M gene are involved in the mastitis susceptibility in dairy cows. (5th December 2013) - Wang, X. G.; Huang, J. M.; Feng, M. Y.; Ju, Z. H.; Wang, C. F.; Yang, G. W.; Yuan, J. D.; Zhong, J. F.
Summary Mutations, such as single nucleotide polymorphisms (SNPs), in the 5′‐flanking and microRNA (miRNA) regulatory regions may result in altered gene expression levels and cause diseases. Alpha‐2‐macroglobulin (A2M) has the function of binding host or foreign peptides and particles, and thereby serves as a defense barrier against pathogens in the plasma and tissues of animals. To investigate the functional markers of the A2M gene associated with mastitis, the promoter was characterized and SNPs that affect promoter activity or binding affinity with the target miRNA were identified using the luciferase reporter assay and real‐time quantitative PCR method. Results showed that the core promoter of A2M was found between the bases g.‐2641 and g.‐2479. Four novel SNPs (g.‐724A>G, g.‐665G>A, g.‐535C>G and g.‐520_‐519insA) in the promoter region were completely linked. The activity of the mutant haplotype (GAGA) increased by 177% compared with that of the wild haplotype (AGC‐). Bta‐miR‐2898 was upregulated by 6.25‐fold in the mammary gland tissues of mastitis‐infected cows compared with that of the healthy cows. One SNP (c.4659_4661delC) located in the 3′‐untranslated region of the A2M gene may affect the binding affinity with the target bta‐miR‐2898. Five SNPs exhibited tight linkage. Association analysis showed that the milk somatic cell score for cows with the mutant haplotype (GAGA‐) was lower than that for cows with the wild haplotype. Thus, the mutant type can be used as a potential functional marker for a mastitis resistance breeding program in dairy cows. Our findings provided the molecular basis for A2M transcriptional and post‐transcriptional regulations. A close relationship between regulatory mutations and mastitis susceptibility of cows also was established.